Organizational socialization, job autonomy and job performance in public secondary schools of Malaysia: Organizational citizenship behavior as mediator - Po, Hui Yee; Liu, Yao (Universiti Malaysia Pahang, 2018)
Teachers are the backbone of education system in Malaysia. The success or failure of educational activities are highly dependent on their job performance. A few comprehensive studies have shown the factors influences employee performance in other sectors but do not adequately represent a significant gap in education. Using a theoretical model based on social exchange theory and job characteristics theory, this study aims to investigate the relationship between organizational socialization, job autonomy and teachers’ job performance considering organizational citizenship behavior in schools (OCBS) as a mediating variable in public secondary schools of Malaysia. Quantitative methodology was used in this study. The study used convenience sampling to select sample of 550 teachers in Malaysia. Questionnaires were used to collect the data. The study used SEM inferential statistical approach where SmartPLS software was selected to run the data analysis. Study findings indicated that OCBS mediated the relationship between organizational socialization and teachers’ job performance. OCBS also mediated the relationship between job autonomy and teachers’ job performance. This study also found that organizational socialization has a direct relationship with teachers’ job performance. The implication of the study is that it is prudent for Ministry of Education or the principals to allow teachers in school to enjoy more autonomy in completing task, create organizational citizenship behavior culture in schools, recognize and value teachers’ voluntary activities and offer mentor-mentee programme in helping new teachers get to know the school better in order to heighten teachers’ job performance in schools. This study elucidated the importance of organizational socialization in impacting job performance of teachers besides showing the importance influence of OCBS in relation to teachers’ job performance.